2021
DOI: 10.1186/s13054-021-03658-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of routine daily blood culture in patients on veno-arterial extracorporeal membrane oxygenation

Abstract: Background Bloodstream infections (BSIs) are frequent on veno-arterial extracorporeal membrane oxygenation (V-A ECMO). Performing routine blood cultures (BCs) may identify early paucisymptomatic BSIs. We investigated the contribution of systematic daily BCs to detect BSIs on V-A ECMO. Methods This was a retrospective study including all adult patients requiring V-A ECMO and surviving more than 24 h. Our protocol included routine daily BCs, from V-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In children, O’Neil et al showed that most infections occurred during the first week and Cashen et al described a similar timing nearly 20 years later [ 4 , 6 ]. Interestingly, in adults, two reports by de Roux et al and Schmidt et al found a similar timing of infection with high incidences during the first 7 days of VA-ECMO [ 13 , 14 ]. Our data supports such timing as well and recommend clinicians to be particularly aware of the risk of infections even during the first days of VA-ECMO support.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In children, O’Neil et al showed that most infections occurred during the first week and Cashen et al described a similar timing nearly 20 years later [ 4 , 6 ]. Interestingly, in adults, two reports by de Roux et al and Schmidt et al found a similar timing of infection with high incidences during the first 7 days of VA-ECMO [ 13 , 14 ]. Our data supports such timing as well and recommend clinicians to be particularly aware of the risk of infections even during the first days of VA-ECMO support.…”
Section: Discussionmentioning
confidence: 84%
“…First, our institutional protocol did not recommend the use of routine blood cultures. Such practice is under debate in the literature, but some interesting data suggest it could be beneficial in certain high-risk situations and it may help to identify earlier bacteriemia [ 13 ]. Second, even if our institutional protocol did not recommend antibiotic prophylaxis, it is notable that the vast majority of patients had in fact an antibiotherapy in place at VA-ECMO initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, blood cultures were not systemically performed in four on 10 patients; thus we could have underestimated the rate of bacteremia. 33 Fifth, surgical cannulation of VA-ECMO as it is performed in our institution is associated with a higher rate of local infection compared to percutaneous cannulation. 34,35 It could lead to a higher rate of infection in our cohort compared to other studies.…”
Section: Discussionmentioning
confidence: 95%
“…Routine surveillance blood cultures are common practice according to an ELSO survey [33], despite past studies not showing any support for this practice [34] and concerns about the potential risk for inappropriate antibiotic treatment for contaminants and increased transfusion requirements after repeated blood extractions. However, a recent retrospective single centre study including 150 patients requiring V-A ECMO support showed that even though routine blood cultures identified significantly less BSI than on-demand clinically prescribed ones, a third of BSI would have been missed by on-demand cultures alone [35 ▪▪ ]. The sensitivity of on-demand cultures improved after identifying and removing patients with risk factors for positivity.…”
Section: Diagnosismentioning
confidence: 99%